Using indaziflam for integrated weed management in managed and natural ecosystems - Seedorf, Rachel H., author; Nissen, Scott, advisor; Tekiela, Daniel, committee member; Schipanski, Meagan, committee member (Colorado State University. Libraries, 2020)
Indaziflam is a relatively new herbicide for natural area weed management. It is unique because it inhibits cellulose biosynthesis and it controls annual weeds as the seeds germinate. This soil active herbicide provides the opportunity to control winter annual grasses and annual broadleaf weeds without impacting established perennial grasses and forbs. These characteristics are key to managing weeds, while promoting the growth of native vegetation. Indaziflam was a key component in the development of an integrated weed management plan for Denver International Airport (DEN). DEN supports a diverse set of landscapes, from the Pena Boulevard Transport Corridor to shortgrass prairie, natural areas, and riparian corridors. DEN is faced with several challenges when managing vegetation, with weed invasion being one of the most important. Kochia (Bassia scoparia) and downy brome (Bromus tectorum L.) pose the greatest threats to desirable vegetation and healthy, sustainable ecosystems. Kochia is an invasive broadleaf that is a prolific seed producer and can spread quickly. Downy brome is also a highly invasive winter annual grass that can fill open niches in native plant communities. Current vegetation management at DEN does not adequately control weeds and does not promote the growth of desirable vegetation. Therefore, site-specific research assessing passive and active restoration practices was conducted to develop a landscape management plan to help improve and promote native vegetation. Two research studies were established at DEN, both with remnant native grasses that were also invaded by downy brome and kochia. The objective was to demonstrate passive restoration. We hypothesized that weed control using indaziflam and other post-emergent herbicides would provide 2+ years of control. Downy brome, kochia, and perennial grass cover and biomass were collected in 2019 and 2020 to measure herbicide impacts and plant community responses. Averaged across both sites, downy brome cover, 2 years after treatment (YAT), was reduced to < 2% in all indaziflam plots compared to the control (~75% cover). At both sites, perennial grass biomass increased 5- to 10 – fold once downy brome competition was removed. These invaded sites with remnant grass populations responded positively with timely weed management. Active restoration was employed at two sites that were void of desirable grass species. Perennial grasses were drill seeded and protected from weed competition with adaptive weed management, primarily with selective herbicides. With adequate weed control and supplemental irrigation, crested wheatgrass was the only grass that successfully established (83% stand frequency). This study illustrates the challenges associated with revegetating degraded sites and the necessity of providing adaptive weed management. Furthermore, the information derived from these studies was used to develop management prioritization categories to assist DEN in making strategic decisions for managing weeds and restoring sites across the airport property. The final management plan represents the culmination of the site-specific, research-based recommendations made and will be utilized by DEN land management to improve current practices. This project also demonstrated the utility of using indaziflam in a managed ecosystem. In natural ecosystems invaded by downy brome, indaziflam provides similar opportunities for passive restoration. Downy brome produces large amounts of litter in these ecosystems that act as continuous fine fuel. Prescribed burning is often used as a tool to remove plant litter and provide downy brome control and can be followed by herbicide treatments to extend control; however, combining prescribed burning with indaziflam has not been evaluated. We hypothesized that removing the litter layer using prescribed fire before applying indaziflam alone or combined with post-emergent herbicides would increase herbicide efficacy and extend downy brome control. In September 2017, two downy-brome infested sites were burned. In March 2018, indaziflam was applied alone or in combination with post-emergent herbicides to the burned area as well as non-burned plots. Downy brome cover and the desirable plant community responses were evaluated to determine burning and treatment effects. Downy brome cover was reduced in all herbicide treatments in the burned plots compared to the non-burned plots at both sites 2 years after treatment (YAT) (Site 1 - 6.5% ± 1.2 SE vs. 19.8% ± 2.6; Site 2 - 7% ± 1.5 vs. 15.5% ± 1.7). Desirable plant species cover, richness, and diversity were not negatively impacted by burning or herbicide treatments. Perennial cool-season grass cover responded positively to burning at site 1, while the perennial forb community responded positively to burning at site 2. Plant diversity and species richness also increased at site 2 in the burned plots which was due to the increase in the number of native forb species. This study demonstrates that burning extended downy brome control even at lower indaziflam use rates, without reducing the diversity of the desirable plant community. This research also demonstrates the utility of using indaziflam in natural ecosystems.
Keywords: indaziflam; species diversity; prescribed burning; downy brome